STUDI SIMPANG BERSINYAL PADA SIMPANG 4 (EMPAT) SEMPAJA SAMARINDA - Galfi, M (KURVA S JURNAL MAHASISWA, 2012)
ABSTRACTOne of the sector in effort develop one of the area is to develop build transportation facilities and basic facilities. Requirement of service activities and public transport will very affecting at its excelsior of ability number of is ownership of motor vehicle and also which motor vehicle and so on is and also supported by change of band road and public transport in town of Samarinda.Referring to the increasing of hour at road street in town of Samarinda resulted progressively increasing it of is ownership of vehicle, and also the limited fund for development in sector of transportation land result not yet functioned decently operation of traffic facility which have been owned.From result of calculation at intersection of Road A.W. Syahranie – Road Wahid Hasyim I – Road Wahid Hasyim II – Road P.M. Noor got by price Degree of Saturation ( DS) at - hour culminate mean above 0,99 where MKJI'97 give number definition of DS maximum is 0,85 will experience of stuck or access intention become is limited. From result which have been concluded by above that performance storey level intersection of Road A.W. Syahranie – Road Wahid Hasyim I – Road Wahid Hasyim II – Road P.M. Noor Samarinda is already can’t to serve current capacities passing it, with factor- primary factor which is influence and have to overcome of with : Driver discipline require to be arranged in order. To arrange collision of conducted by traffic driver of police there must be waking up at hours culminate to observe and overcome the happening of hour and its relevant institution always control light traffic routinely. Keyword : Lamp of Signal, saturation current, Time Saturation cycle, Capacities, Degree of Saturation, and Capacities.